Association of CFAP65 rs56411706 with male infertility in 393 Vietnamese individuals - Thuy Duong Nguyen; Thi Khanh Ly Nguyen; Thi Thu Ha Duong (Vietnam Journal of Science, Technology and Engineering, 2022)
Approximately two thousand genes have been found to be involved in spermatogenesis and their mutations have been reportedly associated with male infertility. Recent studies have shown that CFAP65 was crucial for spermatogenesis, and several mutations in this gene could result in male infertility. However, the association of polymorphisms in CFAP65 with male infertility remains unknown. In this study, the relationship between CFAP65 rs56411706 and male infertility was assessed in a Vietnamese population by 171 male infertility patients who had been diagnosed with non-obstructive azoospermia (NOA), oligozoospermia, or asthenozoospermia while 222 healthy controls were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Statistical analysis demonstrated that the allele frequencies of CFAP65 rs56411706 followed Hardy-Weinberg equilibrium (HWE) (p>0.05). The Chi-square test revealed no correlation between the polymorphism and male infertility in this study (p>0.05). This is the first study on the association between a single nucleotide polymorphism in the CFAP65 gene and male infertility in a Vietnamese population. The results of this study would help enrich the knowledge about the effects of CFAP65 polymorphisms on male infertility in the Vietnamese population.